Copper-chromium contact surface laser remelting method and vacuum circuit breaker

By sandblasting, laser remelting and magnetic grinding on the surface of copper-chromium contacts, the problem of uneven remelting layers of copper-chromium contacts in the prior art is solved, which significantly improves the pressure resistance and breaking ability of the contacts, and enhances the reliability and safety of the vacuum circuit breaker.

CN119549889APending Publication Date: 2025-03-04SHAANXI SIRUI ADVANCED MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411699787.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

In the prior art, when preparing copper-chromium contacts, the microstructure of the remelting layer is uneven and impurities are impurities, which affects the insulation and working performance of the vacuum circuit breaker. The process cost is high and the time is long, which limits the efficiency of large-scale production.

Method used

The laser remelting method on the surface of copper-chrome contacts is adopted, including sandblasting, laser remelting and magnetic grinding, optimize process parameters to form a uniform remelting layer, and improve the pressure resistance and breaking ability of the contacts.

Benefits of technology

Through the optimization of the process, the voltage resistance, breaking capacity and electrical performance of copper-chrome contacts are significantly improved, the service life is extended, and the reliability and safety of vacuum circuit breakers are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549889A_ABST
    Figure CN119549889A_ABST
Patent Text Reader

Abstract

The invention discloses a copper-chromium contact surface laser remelting method and a vacuum circuit breaker. The method comprises the following steps: carrying out sand blasting treatment on a copper-chromium contact; carrying out laser remelting on the copper-chromium contact subjected to sand blasting treatment by adopting a laser printer so as to form a remelting layer on the surface of the copper-chromium contact; and the remelting layer on the surface of the copper-chromium contact is subjected to magnetic grinding, so that the copper-chromium contact with the flat surface is obtained. According to the copper-chromium contact, the electrical performance and the mechanical performance of the copper-chromium contact under the conditions of high voltage and large current can be remarkably improved, and therefore the service life of the copper-chromium contact is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of electrical engineering and material technology, and specifically relates to a copper-chromium contact surface laser remelting method and a vacuum circuit breaker. Background Art

[0002] In the process of preparing copper-chromium contacts in the prior art, especially after the contacts are arc aged, the microstructure of the remelted layer formed is relatively complex and uneven, and even contains some impurities generated during the arc action process. These impurities and uneven grain structure will affect the insulation of the inner wall of the vacuum interrupter, and thus affect the working performance of the vacuum circuit breaker. In addition, in the existing aging process, volatiles may be adsorbed on the tube or magnetic shell, further affecting the insulation performance. Moreover, this process is not only costly and time-consuming, but also increases the production cycle and limits the efficiency of large-scale production. Therefore, the prior art faces challenges in improving the voltage resistance strength, breaking current capability and reducing the cutoff value of the contact material, and it is difficult to fully meet the needs of modern industry for the development of vacuum circuit breakers towards high voltage, large capacity and miniaturization. Summary of the invention

[0003] The main purpose of the present application is to provide a copper-chromium contact surface laser remelting method and a vacuum circuit breaker, and the present application aims to improve the anisotropic performance of the copper-chromium contact.

[0004] To achieve the above objectives, this application provides the following technical solutions:

[0005] A method for laser remelting the surface of a copper-chromium contact comprises: sandblasting the copper-chromium contact; laser remelting the copper-chromium contact after the sandblasting by using a laser printer to form a remelting layer on the surface of the copper-chromium contact; and magnetically grinding the remelting layer on the surface of the copper-chromium contact to obtain a copper-chromium contact with a smooth surface.

[0006] Optionally, the copper-chromium contact is sandblasted under an air pressure of 0.5-1.0 MPa.

[0007] Optionally, the oxygen content in the working chamber of the laser printer is maintained at 100-600 ppm.

[0008] Optionally, the laser remelting time is 10-60s.

[0009] Optionally, the cooling time after laser remelting is 1-2 minutes.

[0010] Optionally, after laser remelting, the thickness of the remelted layer on the surface of the copper-chromium contact is 10-30 μm.

[0011] Optionally, the grinding time of magnetic grinding is 10-20 minutes.

[0012] Optionally, after magnetic grinding, the roughness of the remelted layer on the surface of the copper-chromium contact is 1-3 μm.

[0013] The present application also provides a vacuum circuit breaker, which includes a copper-chromium contact, and the copper-chromium contact is prepared by any of the above-mentioned copper-chromium contact surface laser remelting methods.

[0014] The present application can bring the following beneficial effects: the present application can improve the voltage resistance and breaking capacity of the copper-chromium contacts through optimized sandblasting, laser remelting and magnetic grinding processes, and can significantly reduce the surface roughness of the contacts, thereby significantly improving the electrical and mechanical properties of the copper-chromium contacts under high voltage and high current conditions, extending the service life of the copper-chromium contacts, thereby enhancing the reliability and safety of the vacuum circuit breaker. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is a schematic flow chart of a method for preparing a copper-chromium contact surface by laser remelting provided in one embodiment of the present application;

[0016] Figure 2 This is a schematic diagram of the microstructure of a remelted layer formed after laser remelting of a CuCr25-CuCr55 contact provided in one embodiment of the present application;

[0017] Figure 3 yes Figure 2 A local enlarged schematic diagram of the remelted layer is shown. DETAILED DESCRIPTION

[0018] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] It should be noted that all directional indications in the embodiments of the present invention (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.

[0020] In the present invention, unless otherwise clearly specified and limited, the terms "connection", "fixation", etc. should be understood in a broad sense. For example, "fixation" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0021] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes. Taking "A and / or B" as an example, it includes scheme A, or scheme B, or a scheme that satisfies both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in the field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0022] Figure 1 FIG. 1 is a schematic diagram of a process for preparing a copper-chromium contact surface by laser remelting according to the present application, as shown in FIG. Figure 1 As shown, the method comprises the following steps:

[0023] Step 1: CuCr 25 -CuCr 55 The contact was loaded into the cleaned sandblasting machine and the CuCr 25 -CuCr 55 The arcing surface of the contacts is sandblasted to ensure the CuCr 25 -CuCr 55 The roughness of the contact surface is consistent;

[0024] In this step, the contact surface that has not been sandblasted often has unevenness or microscopic defects. These unevenness will cause diffuse reflection of the laser on the contact surface, thereby reducing the effective utilization rate of the laser energy. Through sandblasting, firstly, the contact surface can be made more uniform and smooth, diffuse reflection can be reduced, and the absorption rate of laser energy can be increased, thereby improving the efficiency and effect of laser remelting. Secondly, sandblasting can remove oxides, oil stains and other impurities on the contact surface, exposing a fresh metal surface and increasing the activity of the contact surface. Thirdly, sandblasting can keep the roughness of the contact surface consistent, thereby ensuring the uniformity of temperature distribution during laser remelting, thereby forming a uniform remelting layer and avoiding defects caused by local overheating or overcooling of the contact.

[0025] Step 2: Sandblasting the CuCr 25 -CuCr 55 The contact is placed on the substrate of the laser printer for laser remelting, wherein the remelting parameters of the laser printer are set as follows: the scanning power is set to 100 W, the scanning speed is set to 800 mm / s, the spot spacing is set to 0.06 mm, the remelting time is set to 10 s, and the cooling is 1 min after the remelting is completed. 25 -CuCr 55 A remelted layer is formed on the contact surface. It should be noted that the thickness of the remelted layer should be maintained between 10-30 μm, thin and uniform, and the size of the Cr particles in the remelted layer is 1-2 μm on average.

[0026] In this step, the CuCr 25 -CuCr 55 Before the contact is laser remelted, the printer's gas washer and fan need to be turned on to ensure that the oxygen content in the working chamber of the laser printer drops below 600ppm and not less than 100ppm (if the oxygen content is greater than 600ppm, the reaction rate of chromium and oxygen will increase significantly, resulting in the formation of chromium oxide (Cr2O3), which is an insulator. Its presence will reduce the conductivity and corrosion resistance of the remelted layer; in addition, if the oxygen content is lower than 100ppm, more complex equipment and stricter control conditions will be required, which will increase the complexity and cost of the process; secondly, the operating time and energy consumption of the gas washer and fan will be increased, thereby increasing production costs). At the same time, argon (Ar) is used to replace the air in the working chamber to prevent the formation of chromium oxide, thereby ensuring CuCr 25 -CuCr 55 Quality and performance of contact surfaces.

[0027] In addition, the minimum effective time of laser remelting is 10s. If the remelting time is too short, the laser energy is insufficient to completely melt the material on the contact surface, resulting in insufficient thickness of the remelted layer, which will affect the uniformity and integrity of the remelted layer, and thus fail to effectively improve the performance of the contact surface. In addition, if the remelting time is too short, the melted material on the contact surface cannot fully flow and solidify, resulting in uneven surface roughness, which cannot reach the required 1-3μm range.

[0028] Step 3: Forming the CuCr with a remelted layer 25 -CuCr 55 The contact is placed in a magnetic grinding machine for magnetic grinding for 10 minutes, and the ground CuCr 25 -CuCr 55 The contacts are cleaned to ensure CuCr 25 -CuCr 55 The roughness (Ra) of the remelted layer on the contact surface is maintained at 1-3 μm.

[0029] In this step, magnetic grinding can further refine the roughness of the contact surface, especially when CuCr 25 -CuCr 55 When the roughness (Ra) of the laser remelted surface of the contact reaches the range of 1-3μm, it helps to improve the CuCr 25 -CuCr 55 Uniformity and smoothness of contact surface, reducing CuCr 25 -CuCr 55 Microscopic unevenness on the contact surface. In addition, the laser remelting process may cause the CuCr 25 -CuCr 55 Tiny burrs or irregular protrusions are formed on the contact surface. These defects can be effectively removed by magnetic grinding, thereby improving CuCr 25 -CuCr 55 The flatness of the contact surface can significantly reduce the risk of arc discharge and increase the CuCr 25 -CuCr 55 The electrical performance of the contact under high voltage and large airflow. More importantly, magnetic grinding is a non-invasive grinding method that drives the grinding medium (such as stainless steel needle) through a magnetic field to grind. It will not cause excessive mechanical damage to the remelting layer and can maintain the integrity and thickness of the remelting layer, thereby ensuring the excellent performance of the contact in the vacuum interrupter.

[0030] It should also be noted that, according to experimental tests, the minimum effective time for magnetic grinding is 10 minutes. If the grinding time is too short (less than 10 minutes), the tiny burrs or irregular protrusions formed during the laser remelting process cannot be fully removed, resulting in the contact surface roughness (Ra) failing to reach the required 1-3μm range. Excessive surface roughness will increase the risk of arc discharge, thereby reducing the electrical performance of the contact.

[0031] In another exemplary embodiment, the present application also provides a method for preparing a copper-chromium contact surface by laser remelting, the method comprising the following steps:

[0032] Step 1: CuCr 25 -CuCr 55 The contact was loaded into the cleaned sandblasting machine and the CuCr 25 -CuCr 55 The arcing surface of the contacts is sandblasted;

[0033] Step 2: Sandblasting the CuCr 25 -CuCr 55 The contact is placed on the substrate of the laser printer for laser remelting, wherein the remelting parameters of the laser printer are set as follows: the scanning power is set to 300W, the scanning speed is set to 1000mm / s, the spot spacing is set to 0.08mm, the remelting time is set to 30s, and the cooling is 1.5min after the remelting is completed. 25 -CuCr 55 A remelting layer is formed on the contact surface. It should be noted that the thickness of the remelting layer should be maintained at 10-30 μm, and the average size of the Cr particles in the remelting layer is 1-2 μm.

[0034] In this step, similarly, when the CuCr 25 -CuCr 55 Before the contact is laser remelted, the printer's gas wash and fan need to be turned on to ensure that the oxygen content in the working chamber of the laser printer drops below 600ppm and not less than 100ppm. At the same time, argon (Ar) is used to replace the air in the working chamber to prevent the formation of chromium oxide, thereby ensuring CuCr 25 -CuCr 55 Quality and performance of contact surfaces.

[0035] Step 3: Forming the CuCr with a remelted layer 25 -CuCr 55 The contact is placed in a magnetic grinding machine for magnetic grinding for 15 minutes, and the ground CuCr 25 -CuCr55 The contacts are cleaned to ensure CuCr 25 -CuCr 55 The roughness (Ra) of the remelted layer on the contact surface is maintained at 1-3 μm.

[0036] In another exemplary embodiment, the present application also provides a method for preparing a copper-chromium contact surface by laser remelting, the method comprising the following steps:

[0037] Step 1: The CuCr 25 -CuCr 55 The contact was loaded into the cleaned sandblasting machine and the CuCr 25 -CuCr 55 The arcing surface of the contacts is sandblasted to ensure the CuCr 25 -CuCr 55 The roughness of the contact surface is consistent;

[0038] Step 2: Sandblasting the CuCr 25 -CuCr 55 The contact is placed on the substrate of the laser printer for laser remelting, wherein the remelting parameters of the laser printer are set as follows: the scanning power is set to 500W, the scanning speed is set to 1500mm / s, the spot spacing is set to 1.0mm, the remelting time is set to 60s, and the cooling is 2min after the remelting is completed. 25 -CuCr 55 A remelting layer is formed on the contact surface. It should be noted that the thickness of the remelting layer should be maintained at 10-30 μm, and the size of the Cr particles in the remelting layer is 1-2 μm on average.

[0039] In this step, the maximum effective time of laser remelting is 60s. If the remelting time is too long, the contact surface material will be over-melted, forming an overly thick remelting layer. An overly thick remelting layer will not only increase the surface roughness, but also may cause defects such as cracks and pores inside the remelting layer. Secondly, the heat affected zone (HAZ) will be expanded, resulting in a decrease in the performance of the contact base material, such as reduced hardness and poor plasticity.

[0040] Step 3: Forming the CuCr with a remelted layer 25 -CuCr 55 The contact is placed in a magnetic grinding machine for magnetic grinding for 20 minutes. Effect of demagnetized stainless steel needle and cleaning agent on ground CuCr 25 -CuCr 55 The contacts are cleaned to ensure CuCr 25 -CuCr 55The roughness (Ra) of the remelted layer on the contact surface is maintained at 1-3 μm.

[0041] In this step, the maximum effective time of magnetic grinding is 20 minutes after experimental verification. If the grinding time is too long (greater than 20 minutes), it will cause CuCr 25 -CuCr 55 Excessive grinding of the contact surface makes the surface too smooth, which is not conducive to electrical contact performance. In addition, excessive grinding can also cause CuCr 25 -CuCr 55 The microstructure of the contact surface changes, which affects the CuCr 25 -CuCr 55 The uniformity and integrity of the remelted layer on the contact surface.

[0042] In the above embodiment, the CuCr 25 -CuCr 55 During the sandblasting process of the contact, the CuCr 25 -CuCr 55 The contact is blasted on the arc surface because: First, within this pressure range, the blasting medium (such as CuCr 25 -CuCr 55 First, the sandblasting medium can impact the contact surface at a sufficient speed to effectively remove oxides, oil stains and other impurities on the surface; second, within this pressure range, the surface roughness after sandblasting can be ensured to be uniform, which is very important for the uniformity of temperature distribution during the subsequent laser remelting process; third, within this pressure range, the impact force of the sandblasting medium on the contact surface is moderate, which can effectively remove surface impurities without damaging the contact substrate.

[0043] It should be noted that, according to experimental verification, if the air pressure is too high (i.e., greater than 1.0MPa), the impact force of the sandblasting medium on the contact surface will be too large, which may cause the contact surface to be excessively rough, or even produce microscopic cracks or pits. The overly rough surface will affect the uniform distribution of temperature during the laser remelting process, resulting in uneven remelting layer and defects. In addition, if the air pressure is too low (i.e., less than 0.5MPa), the impact force of the sandblasting medium will be insufficient. First, the oxides, oil stains and other impurities on the contact surface cannot be effectively removed; second, the roughness of the contact surface after sandblasting may be uneven, affecting the uniform distribution of temperature during the subsequent laser remelting process. The uneven roughness of the contact surface will lead to an uneven remelting layer, thus affecting the performance of the contact.

[0044] In the above embodiment, the average size of the Cr particles in the remelting layer is 1-2 μm, and the thickness of the remelting layer is 10-30 μm, which is the result of careful control and optimization through laser remelting technology. Among them, the Cr particles with a size of 1-2 μm can be evenly distributed in the copper matrix to form a small, uniform, and dispersed structure, avoiding the unevenness and defects caused by large particles. In addition, the fine Cr particles can form more grain boundaries, and the scattering effect of the grain boundaries on the movement of electrons is enhanced, thereby significantly improving the voltage resistance of the contact. Furthermore, the fine Cr particles can effectively reduce the cutoff value of the contact material (the cutoff value refers to the back electromotive force generated by the contact when the current is interrupted, and the fine Cr particles can reduce this back electromotive force), thereby improving the breaking capacity of the contact.

[0045] It should also be noted that a remelting layer thickness of 10-30μm can ensure the uniformity and consistency of the contact surface quality. A remelting layer that is too thin cannot effectively improve the contact surface performance, while a remelting layer that is too thick will increase the contact surface roughness, thereby affecting the electrical performance of the contact.

[0046] In the above embodiment, the CuCr 25 -CuCr 55 The roughness (Ra) of the remelted layer on the contact surface should be kept at 1-3μm. The reasons are: First, when the roughness is within the range of 1-3μm, it can ensure the CuCr 25 -CuCr 55 The microstructure of the contact surface is uniform, which reduces the unevenness and defects of the contact surface, helps to improve the uniformity of the contact surface, and makes the chromium (Cr) particles in the laser remelting layer more evenly distributed, thereby improving the CuCr 25 -CuCr 55 The voltage resistance and breaking capacity of the contact. Second, the roughness of the contact surface directly affects the electrical contact performance. Too high roughness (greater than 3μm) will lead to an increase in the current density at the local contact point, which is easy to cause arc discharge and increase the ablation and wear of the contact. Third, appropriate roughness helps to maintain the microstructure of the remelting layer and avoid stress concentration caused by surface unevenness, thereby improving the voltage resistance of the contact. Fourth, the roughness of the contact surface will affect the cutoff value (the back electromotive force generated by the contact when breaking the current). Appropriate roughness can reduce this back electromotive force, thereby improving the breaking capacity of the contact. In summary, ensuring CuCr 25 -CuCr 55 The roughness (Ra) of the remelted layer on the contact surface is kept in the range of 1-3μm, which can significantly improve the CuCr 25 -CuCr 55 The surface quality and electrical properties of the contacts reduce the risk of arc discharge while optimizing the voltage resistance and breaking capacity of the contacts.

[0047] Figure 2 It is CuCr after laser remelting. 25 -CuCr 55 Schematic diagram of the microstructure characteristics of the contact, Figure 2 It can be seen that CuCr 25 -CuCr 55 The remelted layer on the contact surface presents a uniform structure without obvious defects or holes. The chromium (Cr) particles in the remelted layer are evenly distributed and relatively small in size, with an average size of 1-2μm. Such a microstructure helps to improve the voltage resistance of the contact material, because the fine Cr particles can form more grain boundaries, which enhance the scattering effect of the grain boundaries on the movement of electrons, thereby improving the voltage resistance of the contact.

[0048] Figure 3 yes Figure 2 A local enlarged schematic diagram based on Figure 3 CuCr can be seen 25 -CuCr 55 The Cr particles inside the remelted layer on the contact surface are clearer. These Cr particles are not only small in size but also very evenly distributed, which helps to reduce the cutoff value of the contact material and improve the breaking capacity of the contact. Figure 3 It can also be observed that the interface between the remelted layer and the substrate is smooth, without obvious cracks or other defects, indicating that the laser remelting treatment has a good modification effect on the contact material and can significantly improve the surface quality and electrical properties of the contact.

[0049] Furthermore, the applicant has obtained CuCr by implementing the process described in this application. 25 -CuCr 55 Contact and CuCr obtained by implementing existing process 25 -CuCr 55 The contacts were tested and compared in terms of performance, as shown in Table 1:

[0050] Table 1

[0051] Performance Indicators Existing process This application Cr particle size (μm) 5-10 1-2 Remelting layer thickness (μm) 20-50 10-30 Surface roughness Ra(μm) 5-10 1.0-3.0 Withstand voltage performance (kV / mm) 15 20 Cut-off value (A) 50 30

[0052] As shown in Table 1, the CuCr 25 -CuCr 55 The size of the Cr particles in the contact is 5-10 μm. The CuCr 25 -CuCr 55 The size of the Cr particles in the contact is 1-2 μm. It can be seen that this method can significantly reduce the size of Cr particles through laser remelting and magnetic grinding, and make the distribution more uniform, which is beneficial to improving the voltage resistance and breaking capacity of the contact.

[0053] CuCr obtained by implementing the existing process 25 -CuCr 55 The thickness of the remelted layer of the contact is 20-50 μm. 25 -CuCr 55 The thickness of the remelted layer of the contact is 10-30 μm. It can be seen that this method can make the thickness of the remelted layer more uniform and moderate by precisely controlling the laser remelting parameters, which can effectively improve the surface performance of the contact without increasing the surface roughness.

[0054] CuCr obtained by implementing the existing process 25 -CuCr 55 The surface roughness of the contact is 5-10 μm. The CuCr 25 -CuCr 55 The surface roughness of the contact is 1-3 μm. It can be seen that this method significantly reduces the roughness of the contact surface through sandblasting and magnetic grinding, improves the surface uniformity and smoothness, and reduces the risk of arc discharge.

[0055] CuCr obtained by implementing the existing process 25 -CuCr 55 The withstand voltage performance of the contact is 15kV / mm. The CuCr 25 -CuCr 55 The withstand voltage performance of the contact is 20kV / mm. It can be seen that this method significantly improves the withstand voltage performance of the contact through optimized microstructure and surface treatment, making it perform better under high voltage conditions.

[0056] CuCr obtained by implementing the existing process 25 -CuCr 55 The cut-off value of the contact is 50A. The CuCr 25 -CuCr 55 The cut-off value of the contact is 30A. It can be seen that this method effectively reduces the cut-off value of the contact material and improves the breaking capacity of the contact through the distribution of fine Cr particles.

[0057] In summary, the present invention can significantly improve the microstructure uniformity, surface roughness, withstand voltage and breaking capacity of the copper-chromium contact through sandblasting, laser remelting parameters and magnetic grinding process, so that the CuCr 25 -CuCr 55 The contact has obvious advantages in improving the working performance of the vacuum circuit breaker.

[0058] On the basis of the above embodiments, the present application further provides a vacuum circuit breaker, which includes a copper-chromium contact, and the copper-chromium contact is prepared by the copper-chromium contact surface laser remelting method described in any of the above embodiments.

[0059] The copper-chromium contacts in the prior art are prone to arc discharge under high voltage conditions, which makes the contacts easy to burn and damage. The present application forms a fine and uniform Cr particle distribution on the surface of the copper-chromium contacts after remelting by laser remelting and magnetic grinding. These particles can form more grain boundaries and enhance the scattering effect on electron movement, thereby significantly improving the voltage resistance, breaking capacity, electrical contact performance and service life of the copper-chromium contacts, so that they perform well when applied to vacuum circuit breakers, and can better meet the needs of modern power systems for high voltage, large capacity, miniaturization and high reliability.

[0060] The above are only preferred embodiments of the present application, and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. A method for laser remelting the surface of a copper-chromium contact, characterized in that: The method comprises: Sandblasting of copper-chromium contacts; Using a laser printer to laser remelt the copper-chromium contact after sandblasting to form a remelting layer on the surface of the copper-chromium contact; The remelted layer on the surface of the copper-chromium contact is subjected to magnetic grinding to obtain a copper-chromium contact with a smooth surface.

2. The preparation method according to claim 1, characterized in that: The copper-chromium contact is sandblasted under an air pressure of 0.5-1.0 MPa.

3. The preparation method according to claim 1, characterized in that: The oxygen content in the working chamber of the laser printer is maintained at 100-600ppm.

4. The preparation method according to claim 1, characterized in that: The laser remelting time is 10-60s.

5. The preparation method according to claim 1, characterized in that: The cooling time after laser remelting is 1-2 minutes.

6. The preparation method according to claim 1, characterized in that: After laser remelting, the thickness of the remelted layer on the surface of the copper-chromium contact is 10-30 μm.

7. The preparation method according to claim 1, characterized in that: The grinding time of magnetic grinding is 10-20min.

8. The preparation method according to claim 1, characterized in that: After magnetic grinding, the roughness of the remelted layer on the surface of the copper-chromium contact is 1-3 μm.

9. A vacuum circuit breaker, characterized in that: The vacuum circuit breaker comprises a copper-chromium contact, and the copper-chromium contact is prepared by the copper-chromium contact surface laser remelting method according to any one of claims 1-8.